Is Intracanal Cryotherapy Effective in Reducing Postoperative Endodontic Pain? An Updated Systematic Review and Meta-Analysis of Randomized Clinical Trials - Amal Almohaimede (MDPI AG, 2021)
This research aimed to assess the potency of intracanal cold therapy in diminishing postoperative endodontic pain. PubMed, Scopus, the Cochrane Library, EMBASE, the Web of Science, grey literature, and endodontic journals were used to identify randomized controlled clinical trials evaluating postoperative pain after a final irrigation with a cold irrigant (as an experimental group) and a room temperature irrigant (as a control group). The risk of bias was rated according to the Cochrane Collaboration’s tool and the Grading Recommendation Assessment, Development, and Evaluation (GRADE) system was used to estimate the evidence quality. For the meta-analysis, a random effects model was utilized. The qualitative analysis contained 16 studies and the quantitative analysis contained 9 studies. The experimental groups showed a reduction in postoperative pain at 6 h (mean difference (MD) = −1.11; p = 0.0004; I2 = 72%; low quality evidence), 24 h (MD = −1.08; p = 0.003; I2 = 92%; low quality evidence), 48 h (MD = −0.38; p = 0.04; I2 = 81%; low quality evidence), and 72 h (MD = −0.69; p = 0.04; I2 = 90%; low quality evidence). A higher quality of evidence from more clinical trials is needed.